On the Controlled Loading of Single Platinum Atoms as a Co‐Catalyst on TiO2 Anatase for Optimized Photocatalytic H2 Generation. Issue 16 (3rd March 2020) - Hejazi, Seyedsina; Mohajernia, Shiva; Osuagwu, Benedict; Zoppellaro, Giorgio; Andryskova, Pavlina; Tomanec, Ondrej; Kment, Stepan; Zbořil, Radek; Schmuki, Patrik
Abstract: Single‐atom (SA) catalysis is a novel frontline in the catalysis field due to the often drastically enhanced specific activity and selectivity of many catalytic reactions. Here, an atomic‐scale defect engineering approach to form and control traps for platinum SA sites as co‐catalyst for photocatalytic H2 generation is described. Thin sputtered TiO2 layers are used as a model photocatalyst, and compared to the more frequently used (001) anatase sheets. To form stable SA platinum, the TiO2 layers are reduced in Ar/H2 under different conditions (leading to different but defined Ti 3+ ‐Ov surface defects), followed by immersion in a dilute hexachloroplatinic acid solution. HAADF‐STEM results show that only on the thin‐film substrate can the density of SA sites be successfully controlled by the degree of reduction by annealing. An optimized SA‐Pt decoration can enhance the normalized photocatalytic activity of a TiO2 sputtered sample by 150 times in comparison to a conventional platinum‐nanoparticle‐decorated TiO2 surface. HAADF‐STEM, XPS, and EPR investigation jointly confirm the atomic nature of the decorated Pt on TiO2 . Importantly, the density of the relevant surface exposed defect centers—thus the density of Pt‐SA sites, which play the key role in photocatalytic activity—can be precisely optimized. Abstract : A thin‐film anatase TiO2 substrate for single‐atom (SA) transmission electron microscopy (TEM) characterization is prepared. Control of the surface density of the SA traps results in tunable SA decoration on the anatase surface and superior photocatalytic H2 generation compared to classic noble‐metal‐nanoparticle‐decorated TiO2 .